Observational evidence for the plausible linkage of Equatorial Electrojet (EEJ) electric field variations with the post sunset F-region electrodynamics - V. Sreeja; C. V. Devasia; Sudha Ravindran; Tarun Kumar Pant (Annales Geophysicae, 2009)
The paper is based on a detailed observational study of the Equatorial Spread F (ESF) events on geomagnetically quiet (Ap≤20) days of the solar maximum (2001), moderate (2004) and minimum (2006) years using the ionograms and magnetograms from the magnetic equatorial location of Trivandrum (8.5° N; 77° E; dip lat ~0.5° N) in India. The study brings out some interesting aspects of the daytime Equatorial Electrojet (EEJ) related electric field variations and the post sunset F-region electrodynamics governing the nature of seasonal characteristics of the ESF phenomena during these years. The observed results seem to indicate a plausible linkage of daytime EEJ related electric field variations with pre-reversal enhancement which in turn is related to the occurrence of ESF. These electric field variations are shown to be better represented through a parameter, termed as "E", in the context of possible coupling between the E- and F-regions of the ionosphere. The observed similarities in the gross features of the variations in the parameter "E" and the F-region vertical drift (Vz) point towards the potential usage of the EEJ related parameter "E" as an useful index for the assessment of Vz prior to the occurrence of ESF.